Tuesday
March 28, 2017

Post a New Question

Posted by on .

(Y+3)^2/5+4(Y+3)^7/5=0
solve this equation by factoring. I don't know how to factor problems like this

  • math - ,

    Remember to take out a common factor with the lowest exponent

    (Y+3)^2/5+4(Y+3)^7/5=0
    (y+3)^2/5 [ 1 + 4(y+3) ] = 0
    (y+3)^2.5 (4y + 13) = 0

    (y+3)^2/5 = 0
    y+3 = 0
    y = -3

    or

    4y+13=0
    y = -13/4

Answer This Question

First Name:
School Subject:
Answer:

Related Questions

More Related Questions

Post a New Question